OSSIBILITY STUDY OF KEROSENE FRACTION PRODUCED FROM YEMEN CRUDE OIL AS JET FUEL WITH HIGH QUALITY SPECIFICATION (Journal of Engineering, 2006)
Laboratory investigation and many comparisons between laboratory and commercial samples ofYemeni kerosene distillates were carried out .The physico-chemical properties of the kerosenedistillates were determined . The possibility of their utilization as an aviation turbine fuel with highquality specification " assisting the increase of flight height and velocity " was confirmed . At thefirst look to obtained results , it is shown that the physicochemical properties for all samples are inthe international permissible limits. The carbon content is distributed as the following: 15% normalparaffin ; 50% branched paraffin ; 2% mono-cycloalkanes ; 16% bicycloalkanes ; 16% branchedmono-cycloaromat with branches prevailing ; 1% bicycloaromat . The samples are not hygroscopicfor long period of time . The smoke point is in higher limits standard . Where the freezing point isin lower limits standard .These points prove that the Yemeni kerosene might be prepared for aspectra of jet aircrafts. This Kerosen permit high flying height because it has lower density andfreezing point and it permit high velocity of aviation because it has high percentage of branshed andcyclparaffins with high specific energy without needed for addition of chemical additives, butmay be need for portion of isomers of paraffin.